Green hydrogen production potential for Turkey with solar energy - Karayel, Kubilay; Javani, Nader; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The current study develops a hydrogen map concept where renewable energy sources are considered for green hydrogen production and specifically investigates the solar energybased hydrogen production potential in Turkey. For all cities in the country, the available onshore and offshore potentials for solar energy are considered for green hydrogen production. The vacant areas are calculated after deducting the occupied areas based on the available governmental data. Abundant solar energy as a key renewable energy source is exploited by photovoltaic cells. To obtain the hydrogen generation potential, monocrystalline and polycrystalline type solar cells are considered, and the generated renewable electricity is directed to electrolysers. For this purpose, alkaline, proton exchange membrane (PEM), and solid oxide electrolysers (SOEs) are considered to obtain the green hydrogen. The total hydrogen production potential for Turkey is estimated to be between 415.48 and 427.22 Million tons (Mt) depending on the type of electrolyser. The results show that Erzurum, Konya, Sivas, and Van are found to be the highest hydrogen production potentials. The main idea is to prepare hydrogen map in detail for each city in Turkey, based on the solar energy potential. This, in turn, can be considered in the context of the current policies of the local communities and policy-makers to supply the required energy of each country.(c) 2021 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Green hydrogen; Hydrogen map; PEM electrolyser; Photovoltaics; Solid oxide electrolyser; Solar energy; POWER-TO-GAS; TECHNOLOGIES; Chemistry; Electrochemistry; Energy & Fuels